Pars plana vitrectomy with air tamponade for the treatment of medium‐large macular holes. (17th September 2020) - Cheng, Yan; Zou, Hui; Zhang, Xue; Qi, Shounan; Sun, Fangge; Wang, Chenguang; Liu, Zaoxia
Abstract : Background: To evaluate the surgical outcomes of pars plana vitrectomy (PPV) with air tamponade in medium‐large macular holes (MHs). Methods: Data for 26 eyes of 26 consecutive patients with medium‐large full‐thickness MHs (> 400 μm) who underwent PPV, internal limiting membrane (ILM) peeling, and sterile air tamponade were studied retrospectively. Best‐corrected visual acuity and the closure rate were noted. The follow‐up period was one to 20 months (median, four months). Results: The age range of the patients was 53–73 years (median, 65 years). The mean minimum diameter of the MHs was 550 ± 99 μm. Prior to surgery, 10 eyes (38 per cent) were stage three, and 16 eyes (62 per cent) were stage four. The pre‐operative symptom duration ranged from one month to 24 months (median, four months). Twenty‐four MHs (92.3 per cent) were successfully closed after a single operation. Two (7.7 per cent) patients had a persistent MH. The average visual acuity, calculated as the logarithm of the minimal angle of resolution, improved from 1.44 ± 0.45 pre‐operatively to 0.54 ± 0.29 at the end of the follow‐up period (p < 0.001, paired t‐test). Conclusion: Vitrectomy with ILM peeling and sterile air tamponade is an effective and safe surgical technique for managing medium‐large MHs with a shorter history and does not require intravitreal long‐acting gas tamponade while maintaining a long‐term, face‐down position.